The Risk of Atrial Fibrillation in Patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease - Muhammad Aneel Razzaq; Muhammad Atif; Ubaid Ullah; Mohsin Mehmood; Muhammad Irfan; Kashif Sardar (Life and Science, 2024)
Objective: To evaluate the role of acute exacerbation of COPD in the risk of atrial fibrillation. Study Design: Cross sectional study design. Place and Duration of Study: The study was conducted at Bakhtawar Amin Hospital Multan and Recep Tayyip Erdogan Hospital Muzaffargarh, Pakistan from March 2022 to March 2023. Methods: The patients with acute, hypercapnic chronic obstructive pulmonary disease(COPD) exacerbation were included in the study. A total of 200 patients were analyzed. Baseline data including demographic and clinical details, blood tests, ABG, systolic and diastolic blood pressure, ECG, pulmonary function test, and transthoracic echocardiography were recorded. Results: Of 200 patients, 40(20%) had an episode of paroxysmal atrial fibrillation (AF). Atrial fibrillation was more prevalent in cases with lower FEV1 (P<.05). In addition, it was also more common in cases with higher PaCO2 (P<.05). Atrial Fibrillation was significantly higher in cases with larger LA diameters (34.1 ± 2.3 mm vs 46.1 ± 2.3 mm, P<.05), area (22.8 ± 4.1 cm2 vs 34.1 ± 5.1 cm2, P<.05) and higher PASP (36.1 mmHg ± 2.2 vs 46.4 mmHg ± 3.7, P<.05). RA area was larger in patients with AF and COPD compared to those without AF (25.6 ± 5.1cm2 vs 30.2 ± 6.4 cm2, P<0.05). These findings suggest COPD patients are at increased risk of AF and require measures to reduce the risk. These data will be helpful for further investigation and development of strategies to prevent AF morbidities in COPD patients. Conclusion: In patients with acute exacerbations of chronic obstructive pulmonary disease, blood gas fluctuations, hemodynamic alterations, and abnormal pulmonary functions can lead to an increased risk of atrial fibrillation.